2018
DOI: 10.1002/1878-0261.12409
|View full text |Cite
|
Sign up to set email alerts
|

Intricate crosstalk between MYC and non‐coding RNAs regulates hallmarks of cancer

Abstract: Myelocytomatosis viral oncogene homolog (MYC) plays an important role in the regulation of many cellular processes, and its expression is tightly regulated at the level of transcription, translation, protein stability, and activity. Despite this tight regulation, MYC is overexpressed in many cancers and contributes to multiple hallmarks of cancer. In recent years, it has become clear that noncoding RNAs add a crucial additional layer to the regulation of MYC and its downstream effects. So far, twenty‐five micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 176 publications
(234 reference statements)
1
31
0
Order By: Relevance
“…Transcriptional dysregulation of Myc is among the most frequent events in aggressive tumor cells, 34 endowing cells with physiological changes that have the potential to feedback on RNA production, 35 regulating cell proliferation, migration, apoptosis, and activating vital signaling pathways 33,36,37 . Studies have shown that lncRNAs may function as vital components of the Myc transcriptional network, 37 adding crucial additional layers to the regulation of Myc and its downstream effects 38 . MycLos (Myc‐regulated lncRNAs) functions in cell proliferation and the cell cycle by regulating Myc target genes, such as CDKN1A and CDKN2B 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional dysregulation of Myc is among the most frequent events in aggressive tumor cells, 34 endowing cells with physiological changes that have the potential to feedback on RNA production, 35 regulating cell proliferation, migration, apoptosis, and activating vital signaling pathways 33,36,37 . Studies have shown that lncRNAs may function as vital components of the Myc transcriptional network, 37 adding crucial additional layers to the regulation of Myc and its downstream effects 38 . MycLos (Myc‐regulated lncRNAs) functions in cell proliferation and the cell cycle by regulating Myc target genes, such as CDKN1A and CDKN2B 13 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the roles of lncRNAs in the interaction between HCC cells and TME are mostly unknown (Chen et al , ). The functional mechanisms of lncRNAs are complex and various (Swier et al , ; Yao et al , ). One of the important mechanisms for cytoplasmic lncRNAs is to competitively bind common microRNAs (miRNAs) and relieve the repressive roles of common miRNAs on their targets (Cesana et al , ; Yuan et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In CRC, a MAX/MYC heterodimer induced by elevated HIF-2α mediates transcriptional repression of hypoxia-related miR-15-16, leading to tumor angiogenesis and hematogenous metastasis by further loss of post-transcriptional restriction towards fibroblast growth factor-2 [110]. MYC, also known as MYCC and c-Myc, is frequently amplified in numerous human cancers via transcriptional regulation of specific target genes, including miRNA and lncRNA [111]. MiR-296 − 3p directly targets PRKCA to impair FAK-Ras-MYC signaling, thereby accelerating its own transcription in a FBL that obstructs the EMT signal and progression through the cell cycle, following suppression of cell proliferation, metastasis and chemosensitivity in LUAD [112].…”
Section: Discussionmentioning
confidence: 99%